2022
DOI: 10.1111/jspn.12395
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes management responsibilities between adolescents with T1D and their parents: An integrative review

Abstract: Purpose Diabetes self‐management for adolescents with type 1 diabetes (T1D) is a complex and multifaceted process that requires careful consideration of a supportive or shared approach to care. The purpose of this review was to synthesize the qualitative and quantitative evidence regarding the nature of adolescent−parent interactions and relationships in the context of T1D management. Of particular interest was the role of interdependence in this relationship. Methods An integrative review of the literature wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(140 reference statements)
0
5
0
Order By: Relevance
“…Some of the recommendations for an increased role for healthcare professionals include helping parents to recognize their goals and the independence of the child, adapting consultations and focusing on difficulties perceived by the child but not solely on the health condition (Nightingale et al, 2019). Farthing et al (2022) suggested that healthcare professionals can observe how the parents and children with T1D interact with each other in subsequent visits and integrate the responsibilities of shared T1D management into the overall care plan of the child and the family over time. Future research can explore how the child and their family change through the professional's help.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the recommendations for an increased role for healthcare professionals include helping parents to recognize their goals and the independence of the child, adapting consultations and focusing on difficulties perceived by the child but not solely on the health condition (Nightingale et al, 2019). Farthing et al (2022) suggested that healthcare professionals can observe how the parents and children with T1D interact with each other in subsequent visits and integrate the responsibilities of shared T1D management into the overall care plan of the child and the family over time. Future research can explore how the child and their family change through the professional's help.…”
Section: Discussionmentioning
confidence: 99%
“…The parents in this study appeared to be actively involved in clinic encounters and their contributions were viewed by most providers as essential whilst others felt that parents hindered communication with adolescents. While research studies indicate that parental oversight is problematic when it is ‘over protective’, 5 it is at the same time a strong predictor of adolescents' adherence to diabetes regimen 28,29 . These conflicting findings may be due to differing perceptions/needs, parenting style and adolescents temperament 30 but there is general agreement that maintaining parental involvement in diabetes management during adolescence is critical 29,31 .…”
Section: Discussionmentioning
confidence: 99%
“…While research studies indicate that parental oversight is problematic when it is ‘over protective’, 5 it is at the same time a strong predictor of adolescents' adherence to diabetes regimen. 28 , 29 These conflicting findings may be due to differing perceptions/needs, parenting style and adolescents temperament 30 but there is general agreement that maintaining parental involvement in diabetes management during adolescence is critical. 29 , 31 Parents can find it challenging to balance responsibility whilst promoting their adolescent's autonomy and so providers could help by encouraging parents to gradually ‘step back’ and advising them on how to support their adolescent efforts to engage in clinic encounters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 1 diabetes is characterized by a lack of or near-lack of b-cells, so insulin is necessary for people with this type of diabetes. In addition to hyperglycemia, hypoinsulinism may contribute to other metabolic disorders such as hypertriglyceridemia and ketoacidosis, as well as potentially life-threatening tissue catabolism [1]. Most individuals with type 1 diabetes should be treated with multiple daily injections of insulin or a continuous infusion of subcutaneous insulin.…”
Section: Introductionmentioning
confidence: 99%